The study of the tribe Gastrodieae (Orchidaceae, Epidendroideae) in Sri Lanka I: two new species of Gastrodia - Bandara, Champika; Atthanagoda, Anusha Gayan; Bandara, Nadeesha Lewke; Kumar, Pankaj (Phytotaxa, 2023)
As the first step in the taxonomic study of the tribe Gastrodieae (Orchidaceae), two new species, Gastrodia munasinghae and G. thilakapremae are described here from Sri Lanka based on the distinct morphological differences and long-term field observations. Detailed taxonomic descriptions along with the line drawings, color plates, notes on habitat and ecology, distribution and conservation status, phenology and pollination ecology as well as morphological comparison to the other Gastrodia species in Sri Lanka are also discussed. Both species are endemic to the Island and are assessed as Critically Endangered according to the IUCN Red List criteria. Furthermore, notes are provided along with a distribution map for field identification of all Gastrodia species in Sri Lanka.